Investigation for young adults interest in health - Szoboszlai, Andrea (Journal of Education Culture and Society, 2020)
Young adulthood is a critical period because it is the time when young people begin to live on their own, and adopt health behaviours which can influence their lifestyle and health status. In social practice there are many community belongings and community-ba-sed support systems and programs in health, which aim to increase young adults’ health literacy and offer learning possibilities and support services.The study focuses on the education and the literacy as determinants of health, seve-ral fields of health education and health promotion related to young adults, elements and determinants of health culture, the links between health and learning, adults’ interest and claims related to learning process, methods, topics.In my research I made a survey of learning methods and contents with the help of the analysis of the scientific literature and by questionnaires. I examined young adults’ (18 to 30) concepts of health and healthy lifestyle, motivations, forms of communication, learningmethods and participation in community platforms of health. We use the results of this research to improve programs that support young people’s learning activities for health.